2021
DOI: 10.1002/ece3.8146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multidrug resistance in Pseudomonas spp. isolated from wild bird feces in an urban aquatic environment

Abstract: Antimicrobial resistance (AMR) has been detected in the microbiota of wildlife, yet little is known about the origin and impact within the ecosystem. Due to the shortage of nonepizootic surveillance, there is limited understanding of the natural prevalence and circulation of AMR bacteria in the wild animal population, including avian species. In this surveillance study, feces from wild birds in proximity to the River Cam, Cambridge, England, were collected and Pseudomonas spp. were isolated. Of the 115 samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In particular, P. aeruginosa was detected, respectively, in 10.0% and in 18.3% of birds resident and migratory in line with our study where this bacterium species was the most represented of the ESKAPE group, with a total prevalence of 11.1% (95% CI 6.85–17.1%). In contrast, a recent study conducted in England by Rodrigues et al [ 36 ], reported the presence of Pseudomonas spp. in fecal samples from wild birds with a prevalence of 20.9%, with P. aeruginosa detected in only one bird.…”
Section: Discussionmentioning
confidence: 84%
“…In particular, P. aeruginosa was detected, respectively, in 10.0% and in 18.3% of birds resident and migratory in line with our study where this bacterium species was the most represented of the ESKAPE group, with a total prevalence of 11.1% (95% CI 6.85–17.1%). In contrast, a recent study conducted in England by Rodrigues et al [ 36 ], reported the presence of Pseudomonas spp. in fecal samples from wild birds with a prevalence of 20.9%, with P. aeruginosa detected in only one bird.…”
Section: Discussionmentioning
confidence: 84%
“…As a general trend, counts of CE_ct were significantly lower than those of the extract from spontaneous O. tauricum (CE_st). For Enterobacteriaceae, coliforms, and Pseudomonadaceae, viable counts of CE_ct < 1 Log cfu g −1 suggest a higher hygienic quality of these extracts compared to those prepared from spontaneous O. tauricum (CE_st); this finding might be tentatively ascribed to the differences in the management of cultivated fields than pastures or fallow lands, more often accessed or grazed by wild animals or even livestock, whose feces are known to harbor the aforementioned microorganisms [ 45 , 46 ]. In this regard, recent comparative metagenomic analyses also highlighted the strong influence of farming practices on taxonomic and functional diversity of phyllosphere microbes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that wild birds can carry extended-spectrum β-lactamases (ESBLs) encoded by bla CTX-M and bla SHV from mainly highly pathogenic multidrug-resistant Escherichia coli ( 32 34 ), K. pneumoniae ( 35 ), Pseudomonas spp. ( 36 ), and Campylobacter jejuni ( 37 ) strains. Therefore, wild birds have become an important reservoir host for antimicrobial-resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%